A rare triple tooth in primary dentition: CT findings. Issue 3 (December 2017) - Mergen Gultekin, Irem; Uysal, Serdar; Turgut, Melek Dilek; Dural, Sema; Tekcicek, Meryem
Abstract: Triplication is a rare dental anomaly and defined as the fusion of three teeth. In the present case report, a five-year-old healthy girl with the triplication of the two mandibular primary right incisors along with a supernumerary tooth was presented. A periapical radiograph, panoramic radiograph and cone-beam tomography of the triple tooth revealed separate pulp chambers combining in the cervical area and forming one pulp canal along the root. In the treatment planning, pit and fissure sealant was applied for prevention and the patient was recalled for regular follow-up appointments. After 24 months, the triple tooth had been replaced by the permanent successor without any dental abnormality.